Reflections on a Three-Year-Long Teacher-Centered, Participatory Action Research Experience on Teaching Chemical Bonding in a Swiss Vocational School - Ivano Laudonia; Ingo Eilks (MDPI AG, 2018)
Chemistry is considered to be a difficult subject and chemistry education courses are not very popular among many students. Innovations in the curriculum and pedagogy may help to overcome difficulties in learning as well as motivational problems. Participatory action research (PAR) seems to be a suitable approach for developing such an innovation for the chemistry classroom. This paper reflects on the adoption of a PAR model to teacher-centered action research. A project is discussed aiming at iteratively improving lessons on chemical bonding in a Swiss vocational school. The lesson was focusing on self-determined, autonomous learning in small groups in a multimedia-supported learning environment to foster student motivation for learning. The project is based on the cooperation of a chemistry teacher and a PAR expert group of chemistry teachers operating far away from the school. The cooperation was implemented by synchronous and asynchronous digital communication. The lessons have been cyclically developed over three consecutive years of teaching. The findings from the current study indicate that the implemented practice of action research helped to both improve the teacher’s pedagogical repertoire for his chemistry lessons and contributed to the teacher’s continuing professional development in terms of better understanding how student-centered his lessons should be.